(untitled) (Bangladesh Journal of Medical Microbiology, 2016)
Urinary tract infection (UTI) is the most common nosocomial infection among hospitalized patients. Area-specific monitoring studies aimed to gain knowledge about the type of pathogens responsible for UTIs and resistance pattern of the causative agents may help clinicians to choose correct treatment regimen. So, the present study was aimed to investigate the antibiotic resistance of urinary pathogens isolated at Chittagong Medical College Hospital (CMCH) during January to June, 2007. Out of 360 clinical samples of urine collected, 175 (48.61%) showed significant bacterial growth. The most common pathogens isolated were Escherichia coli (66, 37.71%), Klebsiella species (60, 34.29%), Proteus species (17, 9.71%) and Pseudomonas species (16, 9.14%). Members of the Enterobacteriaceae were 80%-100% sensitive to Imipenem while they were found variably sensitive to other commonly used antibiotics. Pseudomonas species were 100% sensitive to Imipenem, 75% to Amikacin, and 50% to Ceftazidime. Staphylococcus aureus was found 100% sensitive to Vancomycin, 80% to Gentamicin and Amikacin each, and 55% to Oxacillin. Enterococcus species were 80% sensitive to Imipenem, 60% to Ciprofloxacin, 50% to Vancomycin and Amikacin each. The clinicians should use Imipenem selectively in cases of un-responsiveness to commonly used antibiotics. Bangladesh J Med Microbiol 2008; 02 (02): 17-21